Features of approaches of the structure of the national payment system - Mottaeva, A.B.; Niyazbekova, Sh.; Stupak, Ya. (BUKETOV BUSINESS REVIEW, 2023)
Object: The article conducts a study of features of the structure of the national payment system, interaction of its individual elements in their totality. In addition, the authors reviewed the international experience in the field of building a harmonious payment system with a detailed comparison of the domestic and foreign approach, reflected in the illustrative scheme. Methods: The study was conducted using the following methods: General scientific dialectical method of cognition, which was chosen to determine the essence of financial intermediation in general and determine its impact on economic development; - a systematic approach, since the global financial industry is a set of interrelated and interdependent elements, i.e. it shows signs of coherence; The comparative legal approach that is central and necessary in this study to identify common elements of financial services. Findings: No doubt that the payment system has always been the cardio-vascular system of the financial and economic structures. Each nation, whether being born or at stake of collapse, could be characterized by the development of its own payment system and by doing so we can determine if it is thriving or fading away. The abundance of structure components included in the payment system and their complexity always arise scientific interest. The analysis of these peculiarities might carry us to the subset of tendencies and unique features. Hence, the study of European, American and Russian payment systems, scrutinizing their structure and the way scientists define them are the core ideas of this article. As a result, the detailed outcome will be received as comparison will be carried out. Conclusions: During the study it was possible to clearly identify the features of the foreign and domestic approach to the definition of the payment system. In terms of the American and European approaches, the work carried out includes a multi-cluster approach, in which mechanisms, payment and clearing instruments play an important role, Ensuring easy and efficient payment as well as integration into the international remittance system. Considering the ideas of national regulators and institutions responsible for the development of payment infrastructure in general, it is possible to emphasize their subjective approach, as well as their peculiarity in orientation towards the domestic market and cooperation with the EAEU. Significant weight, in turn, here takes the payment infrastructure with relative isolation from the American and European payment systems.